Development of A Herbal-Based Hydrogel: A Promising Approach For Inflammatory Disorders - Singh, Anjali; Jain, Ashish (Journal of Neonatal Surgery, 2025)
Aim: The present study aimed to develop and evaluate a polyherbal hydrogel formulation incorporating hydro alcoholic extracts of Cordio obliqua, Tinospora cardifolia, Lantana camara, Spharanthus indica, and Grewia abutifolia for its anti-inflammatory, antimicrobial, and anti-arthritic activities. Materials and Methods: Six formulations of polyherbal hydrogel were prepared using Carbopol-940, ethanol, propylene glycol, methyl paraben, EDTA, propyl paraben, and triethanolamine. The formulations were characterized for their physical properties, pH, spreadability, viscosity, and swelling index. Anti-inflammatory activity was assessed via protein denaturation and membrane stabilization assays. Antimicrobial activity was evaluated using the well-diffusion method against E. coli, P. aeruginosa, S. aureus, and B. subtilis. In vivo studies, including acute dermal toxicity and anti-arthritic efficacy, were conducted using Freund’s adjuvant and carrageenan-induced paw edema models in rats. Results: The prepared hydrogels were homogenous, translucent, and had a pH range of 6.8-7.3. Formulations PF3 and PF5 exhibited optimal viscosity, swelling index, and spreadability. The in vitro assays demonstrated significant anti-inflammatory activity, with PF5 showing the highest inhibition in protein denaturation and membrane stabilization assays. The hydrogel formulations also exhibited antibacterial activity, particularly against E. coli and S. aureus. In vivo toxicity studies confirmed the gel’s safety, with no observable toxic effects. The anti-arthritic evaluation revealed a reduction in paw edema and joint inflammation in treated groups, with PF5 demonstrating superior efficacy compared to the standard diclofenac sodium gel. Conclusion: The formulated polyherbal hydrogel demonstrated promising anti-inflammatory, antimicrobial, and anti-arthritic properties, supporting its potential as a topical therapeutic agent. The results suggest that PF5 is the most effective formulation for further pharmacological and clinical studies.